The belonging sense to dormitory. Case study: The girl's students of universities in Tehran - z. Anvari (Taḥqīqāt-i Farhangī-i Īrān)
The student dormitory is a semi-public area in which the same age residents involve in intercultural interactions. These interactions can have positive or negative impact in the individual life and also make dependent or independent personality in the future social life decision. Our main question in this article is the study of the belongin sense to the dormitory in the girl’s students. The belonging sense is important because it is the result of desirable condition and influence on trying to improve the living condition. The important factor like security, privacy, positive interaction with the other (roomates and dorm official) and the ruls form the belonging sense. We investigate these factors with studying the 60 life story of girl’s students that live in the dormitory of the universiti’s of Tehran, Tarbiat Modares, Alzahra and Shahid Beheshti. In Final, our results show the belonging sense is low because of lake of privacy, the rules limitation and disagreement with roomates and the dorm offitial. The field of study, the educational level, the culture, and the type of socialization of individuals, age, individual characteristics and ethnicity affect on the sense of belonging to the dormitory.